Fluid sparing effects of chemokine (C-C motif) receptor 1 and 2 antagonists during resuscitation from hemorrhagic shock in rat models - Elizabeth A. Cook; Ololade Ogunsina; Xianlong Gao; Matthias Majetschak (PLoS ONE, 2026)
We described previously that the chemokine (C-C motif) receptor 1 (CCR1) and CCR2 antagonists BX471 and INCB3284 reduce fluid requirements during resuscitation after hemorrhage. Their effects, however, have not been directly compared with each other and consequences of simultaneous blockade of CCR1/2 are unknown. Here we utilized rat (Sprague-Dawley) models of hemorrhagic shock to compare fluid sparing properties when administered individually or in combination and to assess effects on shock tolerance. Series 1: rats were hemorrhaged to a mean arterial blood pressure (MAP) of 30 mmHg for 30 min, followed by blood pressure-directed fluid resuscitation for 6h. At t = 30 min, vehicle (n = 12), BX471 (0.5 µmol/kg, n = 9), INCB3284 (5 µmol/kg, n = 7), or BX471 (0.5 µmol/kg) plus INCB3284 (5 µmol/kg, n = 6) were injected. Series 2: rats were hemorrhaged to a MAP of 30 mmHg for 45 min, injected with vehicle (n = 8), BX471 (0.5 µmol/kg, n = 7) or INCB3284 (5 µmol/kg, n = 5), and observed until t = 225 min. Series 1: cumulative fluid requirements sharply increased between t = 220–300 min and averaged 108±20 mL/kg at t = 390 min with vehicle-treatment. After treatment with BX471, INCB3284 or both, fluid requirements remained constant and averaged 31±8 mL/kg, 51±12 mL/kg and 36.5±8 mL/kg, respectively, at t = 390 min (p < 0.05 vs. vehicle). Mortality was 75% with vehicle treatment and 33%, 57% and 66% with BX471, INCB3284 and BX471 plus INCB3284 treatment, respectively (p > 0.05 vs. vehicle). Measurements of a panel of systemic inflammation markers suggested that BX471 and INCB3284 attenuate release of TNFα and IL6, and enhance release of CCL5 during resuscitation. Series 2: BX471 and INCB3284 treatment did not affect survival times. Our findings confirm fluid sparing effects of BX471 and INCB3284 over 6h of resuscitation, suggest that both drugs exert comparable efficacy to reduce fluid requirements and modulate the systemic inflammatory response to hemorrhage and fluid resuscitation.